The (Domestic) Enforcement of AU International Economic Law Instruments: Exploring the Desirability of Direct Effect - Simo, Regis Yann (The Emergent African Union Law: Conceptualization, Delimitation, and Application, 2021)
This chapter deals with the principle of direct effect as applied in European Union law and explores its suitability in the enforcement of African Union (AU) legal instruments, notably those setting up the African Continental Free Trade Area (AfCFTA). What motivates the issue of direct effect is the noted reticence of African countries to litigate trade matters between themselves despite the existence of provisions of regional trade treaties creating courts of justice which give standing to Member States. Therefore, it surveys the avenues through which natural and legal persons can uphold their rights stemming from AfCFTA treaties thus contributing to treaty interpretation and increasing security and predictability. Currently, the AfCFTA Dispute Settlement Protocol, modelled after the WTO, does not allow such a possibility, contrary to rights acquired by natural and legal persons before some African Regional Economic Communities (RECs) courts. Nevertheless, this chapter finds that carving out access of natural and legal persons to AfCFTA proceedings may not always work as intended since there are other ways to bypass these obstacles. These loopholes could be the gateway through which direct effect will develop and become a principle of AU law broadly speaking. These gaps further complement this chapter’s suggestions to explore amending the AfCFTA legal instruments, even though its dispute settlement system is yet to be tested, in order to match the standing that natural and legal persons have acquired under the RECs, which, in fine, are building blocs towards achieving the AfCFTA and, eventually, the African Economic Community.
Keywords: AfCFTA; Africa; Direct effect; International Economic Law; International Law; International Trade Law; Regional courts; Regional integration

Soft Law in International Investment Law and Arbitration - Adinolfi, Giovanna (The Italian Review of International and Comparative Law, 2021)
In the more recent decades, international investment law (“iil”) and arbitration have been going through a process of recalibration prompted by both the intensification of cross-border capital flows and the States’ growing concerns over the potential restraints iil may impose upon the pursuit of public interests. The present contribution will pay attention to a specific feature that can be observed within these developments, i.e. the role played by soft law in investment arbitration and, more generally, under iil, also with a view to assessing the impact on the formation of binding international law of instruments formally devoid of normative force within the international legal order. After an introduction (Section 1), the contribution is articulated into four sections. Section 2 will first define the field of investigation. The case law of investment tribunals and the treaty practice under the more recent iia s will be then explored as to the reliance on soft law instruments for the purposes of settling procedural (Section 3) and substantive issues (Section 4). Some final remarks will close (Section 5).

Post award arbitral tribunal's mandate under the UNCITRAL Model Law and national laws based thereon - Al Hyari, Omar Hisham; Al Ani, Abdullah Rabee (Heliyon, 2021)
The UNCITRAL Model Law on International Commercial Arbitration provides for the extension of the mandate of the arbitral tribunal post issuance of the final award for the issuance of correction, interpretation, additional award, and remittance of the award back to the arbitral tribunal to remove grounds for challenging the award. Using a doctrinal approach, this paper examines the deviations of the national laws of adopting jurisdictions from the Model Law in regards to this extended mandate, and evaluates the improvements and drawbacks in these deviations. Mainly, the findings of this paper are that, of the many deviations, the positive changes are those that provide comfortable and lenient default provisions for the benefit of inexperienced parties, and since correction, interpretation, additional award, and remittance are useful provisions that are designed to help self-rectify the arbitral process, without adversely delaying it, then the changes that increase the efficacy of these provisions are welcomed. On the other hand, unnecessary deviations are seen as drawbacks that hinder the harmonization of national arbitration laws aimed at by the Model Law. The adopting jurisdictions shall be limited to those acknowledged as such by the UNCITRAL.
Keywords: Additional award; Arbitrage; Arbitragem; Arbitration; Arbitrators' mandate; Award; Correction; Interpretation; Model Law jurisdictions; UNCITRAL Model Law

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

The Impact of Trade Openness and Foreign Direct Investment on Economic Welfare in sub-Saharan Africa - Adegboye, Folasade Bosede; Adesina, Olumide Sunday; Olokoyo, Felicia Omowunmi; Ojeka, Stephen Aanu; Akinjare, Victoria Abosede (International Journal of Financial Research, 2021)
The sub-Saharan African region is characterized by a high relative degree of openness to trade. The region is also identified with increased inflows of foreign investments with no significant welfare improvement. Economic development emphasizes that the lack of domestic investment in the developing economies could be boosted by trade openness and inflow of Foreign Direct Investment (FDI) for impactful enhancement of capital formation. In this article, the impact of trade openness and foreign capital inflow on economic welfare was examined on a sub-regional analysis for sub-Saharan Africa. The study also appraised the effect of openness to trade and FDI inflow on the region's economic welfare. The data for 30 countries from 2000 to 2018 were collected and analyzed, with the Generalized Least Square (GLS) technique to fit the model developed. The study showed that openness to trade has a significant impact on economic welfare for all sub-Saharan Africa regions, while FDI is only significant for the Western sub-region. Hence, the study recommends that the government of the countries in the sub-Saharan Africa region should boost trade openness to enhance efficiency in productivity, and improve industrial development.
Number: 2
Keywords: Economic Welfare; Foreign direct investment; Sub-Saharan Africa; generalized least square; sub-regional analysis; trade openness

Experimenting with international commercial dispute resolution - Erie, Matthew S; Bookman, Pamela K (AJIL Unbound, 2021)
In this essay, we describe the overlapping phenomena of new legal hubs (NLHs), international commercial courts, and arbitral courts. We survey their impact on the law and geopolitics of international commercial dispute resolution, identifying key issues these new dispute resolution institutions raise. While the rise of international commercial courts spans authoritarian and liberal states, Western and Asian states, common law and civil law traditions, it also highlights and builds upon regional differences. We question the assumption that the establishment of new courts is always consistent with an increase in the rule of law, particularly in non-democratic states. We close with thoughts about the potential influence and future role of these institutions. Some of the procedural innovations discussed here may lead to shifts in international commercial dispute resolution for years to come, but the question of whether there is sufficient demand for these new institutions lingers.
Copyright © Pamela K. Bookman, Matthew S. Erie 2021. This is an Open Access article, distributed under the terms of the Creative Commons Attribution licence, which permits unrestricted re-use, distribution, and reproduction in any medium, provided the original work is properly cited.